2020
DOI: 10.1111/epi.16683
|View full text |Cite
|
Sign up to set email alerts
|

Post–COVID‐19 inflammatory syndrome manifesting as refractory status epilepticus

Abstract: There have been multiple descriptions of seizures during the acute infectious period in patients with COVID-19. However, there have been no reports of status epilepticus after recovery from COVID-19 infection. Herein, we discuss a patient with refractory status epilepticus 6 weeks after initial infection with COVID-19. Extensive workup demonstrated elevated inflammatory markers, recurrence of a positive nasopharyngeal SARS-CoV-2 polymerase chain reaction, and hippocampal atrophy. Postinfectious inflammation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(114 citation statements)
references
References 17 publications
1
109
0
4
Order By: Relevance
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
“…Of 13 other patients who had quantitative results for CSF WBC count reported on more than one lumbar puncture, it was unchanged for 2/13 (15%) patients (both ≤6 cells/μL), decreased for 8/13 (62%) patients and increased for 5/13 (38%) patients [ 10 , 45 , 51 , 74 , 77 , 78 , 170 , 180 , 184 , 188 , 205 , 218 , 220 , 233 , 246 ]. The patients whose CSF WBC count increased included 1) a patient with quadriplegia due to Guillain-Barré Syndrome reported by Toscano et al (0 cells/μL➔4 cells/μL 10 days later), 2) a patient with transverse myelitis reported by Munz et al (16 cells/μL➔27 cells/μL after an unspecified timeframe), 3) a patient with encephalopathy for 11 days who had normal intracranial imaging reported by Pilotto et al (18 cells/μL➔38 cells/μL 10 days later), 4) a patient with transverse myelitis reported by Zachariadis et al (16 cells/μL (92% lymphocytes)➔36 cells/μL (94% lymphocytes) and 5) a patient with a leukoencephalopathy 45 days after diagnosis of COVID-19 by nasopharyngeal SARS-CoV-2 PCR (WBC count 1 cell/μL with RBC count 0 cells/μL➔WBC count 2 cells/μL with RBC count 51 cells/μL 1 week later) reported by Carroll et al [ 10 , 45 , 51 , 78 , 220 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, there are reports of patients experiencing symptoms similar to chronic fatigue syndrome after mononucleosis infection, with memory and concentration deficits and profound exhaustion after exertion (Fugl and Andersen 2019 ). Many inflammatory syndromes and responses have been described in recovered COVID patients as well, with patients suffering from neurologic complications such as seizures, Guillain-Barre syndrome, and acute disseminated encephalomyelitis (Carroll et al 2020 ; Chan et al n.d. ; Novi et al 2020 ). Autoinflammatory diseases such as idiopathic thrombocytopenic purpura and autoimmune hemolytic anemia in adults, and pediatric inflammatory multisystemic syndrome, have developed in patients days to weeks after recovery (Zulfiqar et al 2020 ; Galeotti and Bayry 2020 ; Lazarian et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%